Consequences of Misnomer or Mistakes in Identification of Fungal Species - Sasek, Vaclav (International journal of medicinal mushrooms, 2015)
The author, as a reviewer of many international journals, describes his long-standing experiences with incorrect identification of mushroom and fungal species and the resultant incorrect naming of those species that served as experimental models. From his own praxis, he selected several characteristic examples that sometimes ended in a curious situation. Some recommendations to authors of publications and persons responsible for the proper naming of mushrooms under study are summarized.
Keywords: Mycological Typing Techniques; triamcinolonacetonid; History, 20th Century; houby; Nystatin; fixní kombinace léků; gramicidin; mykologické určovací techniky; dějiny 20. století; Fungi; nystatin; Neomycin; Agaricales; History, 21st Century; Gramicidin; neomycin; Triamcinolone Acetonide; dějiny 21. století; Drug Combinations